AKUNTABILITAS DAN TRANSPARANSI PELAPORAN KEUANGAN MASJID (STUDI EMPIRIS: MASJID JAMI DI KOTA BANDA ACEH) - Maulana, Abrar Fauzi; Ridwan, Ridwan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This research is aim to decribe the accountability and transparancy of financial report of the Jami mosque in Banda Aceh. This research is a describtive-qualitative research. This is a natural research in which the events are not conrolled research. The degree of the interference is a minimal interference. This research apllied cross sectional time horizon. The object of this research is Jami mosque in Banda Aceh and the subject of this research is the financial manager and BKM division of Jami mosque. The primary data collected by interview is used in this study. The results of this study indicate in general that the application of accountability and transparancy in the financial reporting of the Jami mosque 'in the city of Banda Aceh has not been implemented.